Evaulation of pigeonpea (Cajanus cajan) varieties for resistance to wilt caused by Fusarium udum and sterility mosaic disease in a perennial system - REDDY, M V; RAJU, T N (The Indian Journal of Agricultural Sciences, 2013)
Fourteen pigeonpea [Cajanus cajan (L.) Millsp.] genotypes were evaluated in a perennial trial for 3 years in a fusarium wilt-and sterility-mosaic disease-screening nursery on a Vertisol, to identify genotypes having resistance to both the diseases. Nine genotypes were found resistant to wilt in the first season, out of which 5 ('ICP 8094', 'ICP 8867', 'ICP 9174', 'PR 5149' and 'ICPL 227') were resistant or moderately resistant in the second season. All the genotypes were susceptible to wilt in the third season. Twelve genotypes showed resistance to sterility-mosaic in all the 3 seasons. This group included the 5 genotypes that showed resistance to wilt in the first and second seasons. Susceptibility to wilt appeared to increase with plant age, whose reasons are to he explored. Grain yields of resistant genotypes in the second season were double (4 000 kg/ha) than those in the first (2Â 000 kg/ha).